Der Besitzdiener: Ein Rechtsinstitut im Wandel der Jahrhunderte - Dietzel, Nicolas (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Since the introduction of the BGB, the “Besitzdiener” has been an important component of German property law. While the groups of persons assigned to the legal institution changed, the legal regulation remained the same. Jurisprudence and literature have also made only minor adjustments to the prerequisites for the definition of the “Besitzdiener”. The norm is therefore under pressure to develop. This paper addresses the question of whether jurisprudence and literature can bring § 855 BGB into the present with respect to its prerequisites - e.g., with respect to the "soziales Abhängigkeitsverhältnis" - and in practice - e.g., with respect to the test drive - or whether a new concept of the “Besitzdiener” is needed.